Primary staging in patients with intermediate- and high-risk prostate cancer: Multiparametric MRI and 68Ga-PSMA-PET/MRI – What is the value of quantitative data from multiparametric MRI alone or in conjunction with clinical information?. Issue 146 (January 2022) - Skawran, Stephan M; Sanchez, Vanessa; Ghafoor, Soleen; Hötker, Andreas M; Burger, Irene A; Huellner, Martin W; Eberli, Daniel; Donati, Olivio F
Highlights: 68 Ga-PSMA-PET/MRI outperformed mpMRI for staging regional lymph node metastasis. Morphometric parameters from mpMRI predicted stage ≥ T3 similar to 68 Ga-PSMA-PET/MRI. The 2018 Briganti model may identify patients who profit from 68 Ga-PSMA-PET/MRI. Abstract: Purpose: Comparing mpMRI and 68 Ga-PSMA-PET/MRI in primary staging of PCa and investigating the value of quantitative mpMRI-measurements for prediction of extracapsular extension and N-metastases. Methods: Patients with PCa undergoing 68 Ga-PSMA-PET/MRI and mpMRI during January 2016 to February 2019 were retrospectively included. Two readers each on 68 Ga-PSMA-PET/MRI or mpMRI rated extraprostatic extension (≥T3) and regional lymph-node-metastasis (N1) on a Likert-scale. A fifth reader measured tumor volume, maximum diameter, and capsular contact length on mpMRI. Probability of lymph-node-metastasis was additionally calculated using the 2018 Briganti model. Interobserver-agreement was assessed by squared Cohen's kappa, and diagnostic accuracy was determined using radical prostatectomy (n = 35/49) as reference standard. Results: 49 patients (median age 66 years [IQR: 61–72 years]) were evaluated. Interobserver-agreement for mpMRI and 68 Ga-PSMA-PET/MRI was: ≥T3: κ = 0.58/0.47; N1: κ = 0.55/0.92. Diagnostic accuracy for mpMRI vs 68 Ga-PSMA-PET/MRI readers for ≥ T3 was AUC: 0.72, 0.62 vs 0.71, 0.72 (p > 0.38) and for N1 was AUC: 0.39, 0.55 vs 0.72, 0.78 (p < 0.01). Quantitative parameters delivered diagnostic accuracies of: AUC: 0.70–0.72 for ≥ T3. The 2018 Briganti model achieved an AUC of 0.89 for N1. Conclusions: Interreader-agreement regarding ≥ T3 was similar for mpMRI and 68 Ga-PSMA-PET/MRI while for N1 it was higher for 68 Ga-PSMA-PET/MRI. Diagnostic accuracy was comparable for ≥ T3 while for N1 it was higher in 68 Ga-PSMA-PET/MRI and the 2018 Briganti model. Combining clinical data and quantitative data from mpMRI in the 2018 Briganti model yielded the highest AUC for prediction of lymph node metastasis and may aid in selecting patients who will benefit from 68 Ga-PSMA-PET/MRI for primary staging.